PERANAN GURU OLAHARAGA TERHADAP GERAKAN SEKOLAH SEHAT PADA SEKOLAH MENENGAH PERTAMA SE-KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH - Berliana, Zernila; Dadang Warta Chanra W.K.; Muhamad Ikhsan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This study aims to examine the role of physical education teachers in the implementation of the School Health Movement (GSS) in SMP Negeri Se-Kecamatan Praya, Central Lombok, during the 2023/2024 academic year. A descriptive survey design was used, and data were collected through questionnaires distributed to 12 physical education teachers from selected schools. The results showed that the role of physical education teachers in implementing GSS was significant, with an average score of 90.58%, categorized as